Living on the edge of America : at home on the Texas-Mexico border - Maril, Robert Lee. (College Station : Texas A & M University Press, 1992)
On the southern edge of America a diverse group of people lead ordinary lives in rather extraordinary circumstances. Mexican Americans, Anglos, and Mexican nationals meet there, in the subtropical beauty of the Rio Grande Valley and amid conditions of extreme poverty and social inequality, and create a distinctive blend of cultures, languages, and attitudes toward life. The stories that emerge are stories of individual victories, daily standoffs, and brutalizing defeats.
Writer-sociologist Robert Lee Maril tells some of these stories, observed and absorbed during the thirteen years he lived and taught in the Lower Rio Grande Valley. In those years, he grew used to the limpid heat, the smell of possum sweating in the moonlight outside his bedroom window, the young men studying to become gasoline mechanics, and the young women walking across the stage as the first in their families to graduate from college. The stories he tells are vivid.
And affecting, filled with palm fronds groaning in a burning wind, bulging pink gecko eyes under the porch light, Mando's karate academy, professors who study rocks and flies, and the small but important victories of junior high students whose families do not speak English. They are stories that recognize the forces at work in people's lives which are beyond their control, but also the qualities of courage, humor, resignation, and sometimes despair that translate those.
Forces in the crucibles of individual lives into unique experiences. The warm, personal accounts that make up this book give a vivid impression of what it is to live in one of the poorest but most intriguing regions of the United States, a region that has much to teach about America's present and future.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
English.
eBooks on EBSCOhost
Keywords: Lower Rio Grande Valley (Tex.) -- Rural conditions -- Case studies; Mexican Americans -- Texas -- Lower Rio Grande Valley -- Social conditions -- Case studies; Mexicans -- Texas -- Lower Rio Grande Valley -- Social conditions -- Case studies; White people -- Texas -- Lower Rio Grande Valley -- Social conditions -- Case studies; Basse vallée du Rio Grande (Tex.) -- Conditions rurales -- Études de cas; Américains d'origine mexicaine -- Texas -- Basse vallée du Rio Grande -- Conditions sociales -- Études de cas; Mexicains -- Texas -- Basse vallée du Rio Grande -- Conditions sociales -- Études de cas; Personnes blanches -- Texas -- Basse vallée du Rio Grande -- Conditions sociales -- Études de cas; SOCIAL SCIENCE -- Anthropology -- Cultural; SOCIAL SCIENCE -- Discrimination & Race Relations; SOCIAL SCIENCE -- Minority Studies; Mexican Americans -- Social conditions; Mexicans -- Social conditions; Rural conditions; White people -- Social condition; Texas -- Lower Rio Grande Valley; Case studies